Zinc Oxide–Coated Poly(HIPE) Annular Liners to Advance Laser Indirect Drive Inertial Confinement Fusion. (17th February 2018) - Fitzsimmons, Paul; Elsner, Fred; Paguio, Reny; Nikroo, Abbas; Thomas, Cliff; Baker, Kevin; Huang, Haibo; Schoff, Mike; Kaczala, David; Reynolds, Hannah; Felker, Sean; Farrell, Mike; et al.
Abstract: Laser indirect drive is hindered, in part, by two problems: "wall motion" resulting from ablation of the hohlraum inner wall and "preheat" of the fuel capsule. To mitigate wall motion and preheat, a mid-Z–coated high internal phase emulsion, poly(HIPE) foam liner (5.7-mm diameter, 150 μm thick, 2.8 mm long, 33 mg/cm 3 ) was developed and integrated into the hohlraum interior. A zinc oxide coating was applied throughout the poly(HIPE) foam using atomic layer deposition to achieve 149 ± 14 mg/cm 3 bulk density. Preliminary data collected from actual shots at the National Ignition Facility suggest the inclusion of the poly(HIPE) liner reduced preheat threefold and stimulated Brillouin scattering (SBS) fivefold relative to an existing reference shot on a gold hohlraum (wavelength shift also contributed to SBS reduction).